Does carbon dioxide insufflation impact adenoma detection rate? A single-center retrospective analysis - Perbtani, Yaseen B.; Riverso, Michael; Shuster, Jonathan J.; Chakraborty, Joydeep; Brar, Tony S.; Agarwal, Mitali; Zhang, Han; Gupte, Anand; Chauhan, Shailendra S.; Forsmark, Christopher E.; Draganov, Peter V.; Yang, Dennis (Endoscopy International Open, 2016)
Background and study aims: Carbon dioxide (CO2) has been associated with reduced post-procedural pain and improved patient satisfaction when compared to air insufflation (AI). The effect of CO2 insufflation (CO2I) on the adenoma detection rate (ADR) remains unclear. The aims of this study are to compare ADR in patients undergoing screening colonoscopy with AI vs. CO2I and identify predictors of ADR.Patients and methods: Single-center retrospective cohort study of 2,107 patients undergoing screening colonoscopy at the University of Florida Hospital between November 2011 and June 2015. Patient demographics, procedural parameters, and histology results were retrospectively obtained from a prospectively maintained colonoscopy database. Univariate and multivariate analysis were performed to identify predictors of ADR. Results: A total of 2107 colonoscopies (644 with AI and 1463 with CO2I) were analyzed. Overall ADR was 27.8 %. There was no significant difference in ADR between AI (27.6 %) vs. CO2I (27.8 %) (P = 0.93). Method of insufflation (AI vs. CO2I) was not significantly associated with ADR (OR 0.9; 95 % CI:0.7 – 1.2). Older age (OR: 1.02; 95 % CI: 1.001 – 1.03 per year increase), male gender (OR 1.48; 95 % CI: 1.17 – 1.87), and longer scope withdraw time (OR 1.13; 95 % CI: 1.1 – 1.16 per minute) were associated with a higher ADR. Fellow involvement was negatively associated with ADR (OR 0.60; 95 % CI: 0.47 – 0.77). Conclusion: ADR was similar between patients who underwent screening colonoscopy with AI vs. CO2I. While CO2I has been associated with improved patient comfort and post-procedural recovery time, there is no definitive evidence to suggest that this method of luminal distention enhances ADR.